ANALYSIS OF SUGENO'S FUZZY INFERENCE SYSTEM IMPLEMENTATION TO DETERMINE THE NUMBER OF GOODS ORDERS AT SUZUYA SUPERMARKET - Hendrik K. Laoli; Annisa Maulida; Jegedis Pri; Yonata Laia (Sean Institute, 2022)
Currently, supermarkets in Indonesia had become a shopping place in great demand by the public, in terms of strategic location, also with the types of goods available such as food that people need every day. With so many shopping enthusiasts to supermarkets such as Alfamart, Suzuya then every types of goods there were a lot that must be done to increase the stock of goods to remain available, but because the number of types of goods would be provided, employees for the stock of goods were overwhelmed in checking the stock of goods would be carried out additional stock. Therefore, there needs to be a system that would help every employees work in the supermarket, especially those who did the stock recording of goods in warehouse employees. In this study, analyzed Sugeno's Fuzzy Inference System in order to provide effective and efficient work in the ordering section of goods supplied at supermarkets. The results of this study concluded that using Sugeno's Fuzzy Inference System system was faster in determining the stock to be provided to supermarkets